2016
DOI: 10.1590/1679-78252934
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Analysis of Rotating Functionally Graded Cylindrical Shells with Orthogonal Stiffeners

Abstract: In this paper, free vibration analysis of rotating functionally graded cylindrical shells with orthogonal stiffeners is presented. Based on Love's first approximation theory and smeared stiffeners technique, the governing equations of motion which take into account the effects of initial hoop tension and also the centrifugal and Coriolis forces due to rotation are derived. The influence of the power law index, the stiffener's height-to-width ratio, the circumferential wave numbers, the shell length-to-radius r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…Những năm gần đây, có một số tác giả đã công bố các bài báo về vỏ trụ tròn làm bằng vật liệu FGM có gân gia cường vòng như các tác giả [14,15]. Một hướng nữa là phân tích dao động vỏ trụ tròn FGM có gân gia cường và quay như trong các nghiên cứu [16][17][18]. Trong bài báo này, tác giả tập trung vào phân tích dao động của vỏ trụ tròn FGM có gân gia cường trực giao (cả gân vòng và dọc) bằng việc sử dụng kỹ thuật san đều tác dụng gân Lekhnitskii, và áp dụng lời giải Navier cho bài toán vỏ trụ tròn có biên tựa khớp tại hai đầu.…”
Section: Giới Thiệuunclassified
See 1 more Smart Citation
“…Những năm gần đây, có một số tác giả đã công bố các bài báo về vỏ trụ tròn làm bằng vật liệu FGM có gân gia cường vòng như các tác giả [14,15]. Một hướng nữa là phân tích dao động vỏ trụ tròn FGM có gân gia cường và quay như trong các nghiên cứu [16][17][18]. Trong bài báo này, tác giả tập trung vào phân tích dao động của vỏ trụ tròn FGM có gân gia cường trực giao (cả gân vòng và dọc) bằng việc sử dụng kỹ thuật san đều tác dụng gân Lekhnitskii, và áp dụng lời giải Navier cho bài toán vỏ trụ tròn có biên tựa khớp tại hai đầu.…”
Section: Giới Thiệuunclassified
“…Dựa trên kỹ thuật san đều tác dụng gân Lekhnitskii, bỏ qua thành phần xoắn của gân, chúng ta đạt được biểu thức của các thành phần ứng lực của vỏ trụ tròn có gân gia cường như sau, theo [16,19,20]: Đối với vật liệu FGM, ta có quan hệ ứng suất -biến dạng:…”
Section: Cơ Sở Lý Thuyếtunclassified
“…There are several approaches to the introduction of stiffeners. For example, in Kidane et al (2003) andJaunky et al (1996, a discrete approach is singled out, which can be found, for example, in Qu et al (2013), Amiro and Zarutskii (1983), Huang and Qiao (2020), Khalmuradov and Ismoilov (2020), Lee and Kim (1998), Mustafa and Ali (1989), Sadeghifar et al (2011), Talebitooti et al (2010, Wang et al (1997), Wang and Hsu (1985) and Zhao et al (2002), as well as an approach with stiffness smearing (Efimtsov and Lazarev (2009), Jaunky et al (1996), Bich et al (2013), Buragohain and Velmurugan (2009), Srinivasan and Krishnan (1989), Totaro (2016), Tu and Loi (2016), etc. ).…”
Section: Introductionmentioning
confidence: 99%
“…Many works have been performed on the static and dynamic behaviors of FGM structural components in recent years. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] To apply the functionally graded (FG) beam structures widely into the engineering practice, an in-depth understanding of their both linear and nonlinear behaviors is essential. In the existing literature, it is found that many researchers have paid their attention to studying on linear behaviors of the FG beams.…”
Section: Introductionmentioning
confidence: 99%